Cytokine‐Driven Hyperinflammation in Long COVID: Mechanisms, Biomarkers, Complement Dysregulation, and Emerging Immunotherapies—A Narrative Review - Emmanuel Ifeanyi Obeagu (Health Science Reports, 2026)
ABSTRACT Background and Aims Long COVID, also known as post‐acute sequelae of SARS‐CoV‐2 infection (PASC), is a multisystem condition characterized by persistent symptoms that continue beyond the acute phase of infection. Growing evidence indicates that sustained immune dysregulation involving cytokine‐mediated inflammation, complement activation, endothelial dysfunction, thromboinflammation, and viral antigen persistence contributes to its pathogenesis. This narrative review summarizes current evidence on the mechanisms underlying hyperinflammation in Long COVID, highlights emerging biomarkers, and evaluates evolving immunotherapeutic strategies. Methods A narrative literature search was conducted using PubMed, Scopus, Web of Science, Embase, and Google Scholar for studies published between 2020 and 2026. Priority was given to systematic reviews, meta‐analyses, cohort studies, mechanistic investigations, and clinical trials examining immune dysregulation, inflammatory biomarkers, complement pathways, and targeted therapies in long COVID. Results Persistent elevation of pro‐inflammatory cytokines, including interleukin‐6, interleukin‐1β, tumor necrosis factor‐α, interferon‐γ, and interleukin‐17, together with activation of the alternative and lectin complement pathways, contributes to endothelial injury, microvascular thrombosis, neuroinflammation, fibrosis, and multisystem dysfunction. Emerging biomarkers include inflammatory cytokines, complement proteins, endothelial activation markers, coagulation indices, and multi‐omics signatures that may improve disease stratification and therapeutic monitoring. Investigational therapies include cytokine‐targeted biologics, complement inhibitors, Janus kinase inhibitors, mesenchymal stem cell therapy, microbiome‐directed interventions, and precision immunotherapy. Conclusion Long COVID results from complex interactions between persistent inflammation, complement dysregulation, vascular injury, and immune dysfunction. Integrating validated biomarkers with precision immunotherapeutic approaches may improve diagnosis, risk stratification, and individualized management. However, robust prospective studies and randomized clinical trials remain essential to validate these strategies and optimize long‐term clinical outcomes.